Describing Ethiopian Bookbinding in TEI - Eliana Dal Sasso (Journal of the Text Encoding Initiative)
Ethiopian bookbinding is one of the material expressions of the ancient manuscript culture of Ethiopia and Eritrea, which is the research field of the Beta maṣāḥǝft project. Despite the significance of the materials and techniques adopted in bookbinding manufacture for the understanding of the manuscript they enclose, they have never been systematically recorded, until very recently. The present paper introduces the Beta maṣāḥǝft project’s innovative approach to bookbinding descriptions and its customization of the TEI schema to record the small variations of Ethiopian bookbinding elements. Since a standard vocabulary for Ethiopian bookbinding features was lacking, Beta maṣāḥǝft developed a tailored taxonomy to create consistent descriptions. The encoding of the binding occurs in the element, within which a element is assigned to each significant bookbinding feature. The descriptions consist partly of free text and partly of markup using keywords enforced by the taxonomy. This paper presents some applications offered by the Beta maṣāḥǝft project that use the recorded bookbinding features, and it shows how the encoding of this large amount of previously ignored data could open new research perspectives on Ethiopian book production.